Research on effects of training programs in judo - Salaj, S.; Milanovic, D. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
Methodological research in sport is focused on the analysis of effects diverse training methods as well as effects of training programmes have on athletes` performance and on their states in particular stages of fitness and sports form development across typical cycles of both the annual and perennial periodization. Unfortunately, the fewest scientific evidences have so far been provided of the efficiency of certain exercise and teaching methods. Investigations are needed to obtain information on the most quality methods for in conjunction with age, gender and quality level of athletes in particular cycles of both the annual and perennial periodization.